Preface - Othman, Jamal (Unit Penerbitan JSKM, 2025)
The SIG CS@e-Learning committee would like to express its deepest appreciation to the dedicated educators from the Department of Computer Science & Mathematics (Jabatan Sains Komputer & Matematik, JSKM), Universiti Teknologi MARA (UiTM), Penang Branch, for their unwavering commitment and valuable contributions in bringing the ninth edition of this publication to life. Their tireless efforts and scholarly passion have played a pivotal role in upholding the quality and integrity of this academic endeavor. This edition successfully garnered a total of 21 high-quality scholarly articles, all of which met the established criteria and were accepted for publication after a rigorous review process. The diversity of topics and depth of research showcased in this volume reflect the dynamic nature of e-learning and the increasing interest in digital education methodologies among educators and researchers. Authors are highly encouraged to continue enhancing their work by integrating further insights, expanding discussions, and addressing emerging challenges. These efforts will not only strengthen the academic value of their research but also open avenues for publication in reputable, high-impact journals indexed by SCOPUS, Web of Science (WOS), or Excellence in Research for Australia (ERA). Looking ahead, the theme for the upcoming tenth volume, “The New Frontiers of E-Learning: Shaping the Future of Education,” highlights the ever-evolving landscape of digital learning technologies and pedagogies. Over the past few decades, e-learning has proven to be a transformative force in education—reshaping how knowledge is delivered, accessed, and applied. Its remarkable adaptability, coupled with the rapid advancement of mobile and internet technologies, has enabled e-learning to transcend traditional classroom boundaries. Today, digital learning plays an integral role not only in higher education and vocational training but also in primary and secondary education, offering flexible and inclusive learning opportunities to a wide range of learners.